Pengaruh Penambahan Limbah Ampas Kopi Terhadap Kuat Geser pada Tanah - Almiga Kristha Lestin; Meti; Ika Apriyani (Paulus Civil Engineering Journal, 2022)
In a construction, be it a building, a land transportation building or a water building, there is a supporting land. If the soil used has good characteristics then it does not need to get special attention, but as we know not all soils have the same characteristics and some are even bad which if used for a construction can result in a construction failure. From this understanding, a study aimed at improving soil quality will be tried, namely by using coffee grounds waste for added materials which will later be tested to see and find out how much influence it has on increasing cohesion and shear angles. The purpose of this study was to determine the physical properties of the soil and to determine the effect of adding coffee residues on soil supplied from the slow mamasa regency with a direct shear test. The methods carried out on this study used experimental studies. The results showed that each soil sample mixed with coffee grounds in the composition of addition by 5%, 10% and 15% experienced an increase in the cohesion value (c) and the shear angle value (φ).